2004
DOI: 10.1002/fld.662
|View full text |Cite
|
Sign up to set email alerts
|

Development of a fully coupled control‐volume finite element method for the incompressible Navier–Stokes equations

Abstract: SUMMARYThis paper proposes and investigates fully coupled control-volume ÿnite element method (CVFEM) for solving the two-dimensional incompressible Navier-Stokes equations. The proposed method borrows many of its features from the segregated CVFEM described by Baliga et al. Thus ÿnite-volume discretization is employed on a colocated grid using either the MAW or the FLO schemes and an element-by-element assembling procedure is applied for the construction of the discretizations equations. In this paper, and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Because the cost per iteration is higher for the coupled solver, it is more meaningful to compare the CPU time consumed by both solvers. Results in Table 3 indicate that as the grid size increases from 10 4 to 3 Â 10 5 quadrilateral (triangular) control volumes, the corresponding ratio of the CPU time needed by the segregated solver to the CPU time required by the coupled algorithm increases from 13 to 115 (13-104), 18 to 71 (8-58), 4 to 31 (3-33), 8 to 56 (6-54), 8 to 22 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and 5 to 38 for the above problems. This represents a tremendous savings as the total time required by the coupled approach to solve all problems on the coarsest and densest quadrilateral (triangular) grids used are 209.6 and 11660.1 (339.7 and 12849.3) seconds while the times required by the segregated method are 1844.89 and 525911.74 (2113.11 and 564206) seconds with the average S/C ratio varying from 8.8 to 45.1 (6.22-43.9).…”
Section: Comparison Of Performance Of the Coupled Solver With The Segmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the cost per iteration is higher for the coupled solver, it is more meaningful to compare the CPU time consumed by both solvers. Results in Table 3 indicate that as the grid size increases from 10 4 to 3 Â 10 5 quadrilateral (triangular) control volumes, the corresponding ratio of the CPU time needed by the segregated solver to the CPU time required by the coupled algorithm increases from 13 to 115 (13-104), 18 to 71 (8-58), 4 to 31 (3-33), 8 to 56 (6-54), 8 to 22 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and 5 to 38 for the above problems. This represents a tremendous savings as the total time required by the coupled approach to solve all problems on the coarsest and densest quadrilateral (triangular) grids used are 209.6 and 11660.1 (339.7 and 12849.3) seconds while the times required by the segregated method are 1844.89 and 525911.74 (2113.11 and 564206) seconds with the average S/C ratio varying from 8.8 to 45.1 (6.22-43.9).…”
Section: Comparison Of Performance Of the Coupled Solver With The Segmentioning
confidence: 99%
“…In the second approach a pressure equation is derived either through the addition of pseudo-velocities [23] as in the segregated SIMPLER algorithm [24] or without the addition of new variables [25] as in the segregated SIMPLE algorithm [9]. Following either method, a set of diagonally dominant equations is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The successive substitution method has been traditionally used with segregated solvers for the Navier-Stokes equations. To the authors' knowledge, only Deng et al [3,11] and Ammara and Masson [4] have used such a method for coupled solvers. The application of the Picard procedure to a coupled system implies the solution of larger linear systems when compared with segregated ones (and, therefore, a greater computational cost), but additional cycles due to the coupling of the transport equations are avoided.…”
Section: Linearization Procedures and Dual-time-stepping Integrationmentioning
confidence: 97%
“…Their proposal is to add a new set of unknowns (the so-called pseudo-velocities) for implementing the discretization of the pressure equation without increasing the size of the computational molecule. Ammara and Masson [4] carried out a comparison with segregated formulations and found that their proposal was more efficient for all the problems studied (and the gain became greater for larger meshes). Density-based algorithms are extended to low-Mach flows by using the pseudo-compressibility technique [5], which is based on including an artificial transient term for pressure in the continuity equation, viz., ð1=b c Þ qp=qt.…”
Section: Introduction/motivation/backgroundmentioning
confidence: 96%
See 1 more Smart Citation